Maintenance of Safety Behaviors via Response-Produced Stimuli. (November 2015) - Angelakis, Ioannis; Austin, Jennifer L.
Animal studies suggest that safety behaviors may be maintained by internally or externally produced safety signals, which function as positive reinforcers. We designed two experiments to test this phenomenon with humans. Participants played a computerized game in which they could earn or lose treasures by clicking on a map. In baseline, losses could be postponed by pressing a pedal that also produced a blue bar at the bottom of the screen. During test conditions, no losses were programmed, and pedal presses turned the bar from yellow to blue (Test 1) or blue to yellow (Test 2). In Experiment 2, new participants were exposed to the same conditions but were given information about the safety of the test environment. In both experiments, participants engaged in high rates of pedal pressing when presses were followed by blue bars, suggesting the bar functioned as a safety signal. We discuss how these findings may relate to safety behaviors commonly observed in certain mental health disorders.